Examining the Dark Side of Financial Markets: Do Institutions Trade on Information from Investment Bank Connections? - Griffin, John M.; Shu, Tao; Topaloglu, Selim (Review of Financial Studies, 2012)
Institutions often have access to corporate inside information through their connections, but relatively little is known about the extent to which they exploit their informational advantage through short-term trading. We employ broker-level trading data to systematically examine possible cases of connected trading. Despite examining the issue from multiple angles, we are unable to find much evidence to support that investment bank clients take advantage of connections through takeover advising, IPO and SEO underwriting, or lending relationships. In contrast to recent academic literature and popular press, our findings suggest that institutional investors are reluctant to use inside information in traceable manners.